Impact of Job Satisfaction and Organizational Culture on Company Performance - Ashabulkafhi Idris (P3M STIEM BONGAYA, 2021)
Objectively, this study aims to examine and analyze the effect of job satisfaction and organizational culture on employee performance. This study involved 54 respondents from employees at the ASN Health Office in Gowa Regency. The research data was collected through distributing questionnaires and processed with the help of SPSS. Several stages of testing will be carried out to test the quality of the data and test the research hypothesis. The research data will be tested using classical assumptions in normality, multicollinearity, heteroscedasticity, and autocorrelation. The results showed that job satisfaction has a positive and significant effect on employee performance, that organizational culture has a positive and significant impact on employee performance. That job satisfaction and corporate culture simultaneously affect employee performance.